A MODEL OF MANAGEMENT STRATEGY FOR A QUALITY LEARNING IN ISLAMIC HIGHER EDUCATION (IHE) - Hidayat, Ara; Sajidin, Sajidin (Jurnal Pendidikan Islam, 2016)
The quality of Islamic education is generally influenced by several factors, among other things: leadership, organizational culture, lecturercompetence versus faculty student ratio, dynamic curriculum, library collections and learning facilities. The factors above are most likely to influence and impact the quality of education process in general. Developing a model of management strategy for quality learning is a minimal effort to improve quality graduates of a university. The model was developed on the basis of the following theories: (1) transformative leadership (Tichy and Devana (1997), (2) strategy of learning organization, (Peter (2002), and (3) a quality-based management (Griffin, 2004). Furthermore, the model shares the following characteristics: (1) a quality learning emerges from an effective and efficient management of academic service; (2) developing management of a quality learning is continuous lecture development; (3) lecture plays an important role in developing a quality learning; (4) a quality learning stipulates that a leader be loyal and committed to their job, wise and have a sense of democracy.